Membrane assemblages for dialysis separation of solutes - Chu, Richard Q. (Philippine Engineering Journal)
This paper examines the performance of several configurations dialysis units for the separation of two solutes. Dialyzers arranged in series, in parallel and the continuous column in countercurrent flow are studied. The single dialysis unit is also included. For the recovery of the less permeable solute, the series configuration can give a good performance. The parallel configuration favors the recovery of the more permeable component. The continuous column has better capabilities for the separation and recovery of both the more permeable component and the less permeable component.